Barriers to hydroxyurea use from the perspectives of providers, individuals with sickle cell disease, and families: Report from a U.S. regional collaborative - Treadwell, Marsha J.; Du, Lisa; Bhasin, Neha; Marsh, Anne M.; Wun, Theodore; Bender, M. A.; Wong, Trisha E.; Crook, Nicole; Chung, Jong H.; Norman, Shannon; Camilo, Nicolas; Cavazos, Judith; et al. (Frontiers in Genetics, 2022)
Sickle cell disease (SCD) is an inherited blood disorder that affects about 100,000 people in the U.S., primarily Blacks/African-Americans. A multitude of complications negatively impacts quality of life. Hydroxyurea has been FDA approved since 1998 as a disease-modifying therapy for SCD, but is underutilized. Negative and uninformed perceptions of hydroxyurea and barriers to its use hinder adherence and promotion of the medication. As the largest real-world study to date that assessed hydroxyurea use for children and adults with SCD, we gathered and analyzed perspectives of providers, individuals with SCD, and families. Participants provided information about socio-demographics, hospital and emergency admissions for pain, number of severe pain episodes interfering with daily activities, medication adherence, and barriers to hydroxyurea. Providers reported on indications for hydroxyurea, reasons not prescribed, and current laboratory values. We found that hydroxyurea use was reported in over half of eligible patients from this large geographic region in the U.S., representing a range of sickle cell specialty clinical settings and practices. Provider and patient/caregiver reports about hydroxyurea use were consistent with one another; adults 26 years and older were least likely to be on hydroxyurea; and the likelihood of being on hydroxyurea decreased with one or more barriers. Using the intentional and unintentional medication nonadherence framework, we found that, even for patients on hydroxyurea, challenges to taking the medicine at the right time and forgetting were crucial unintentional barriers to adherence. Intentional barriers such as worry about side effects and “tried and it did not work” were important barriers for young adults and adults. For providers, diagnoses other than HgbSS or HgbS-β0 thalassemia were associated with lower odds of prescribing, consistent with evidence-based guidelines. Our results support strengthening provider understanding and confidence in implementing existing SCD guidelines, and the importance of shared decision making. Our findings can assist providers in understanding choices and decisions of families; guide individualized clinical discussions regarding hydroxyurea therapy; and help with developing tailored interventions to address barriers. Addressing barriers to hydroxyurea use can inform strategies to minimize similar barriers in the use of emerging and combination therapies for SCD.